The Role Of Leadership And Discipline On Employee Performance - Puspita Puji Rahayu (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This study seeks to examine the impact of the work environment, leadership, and work discipline on the performance of PT personnel. Mount Merbabu Semarang Branch Office operates partially and simultaneously. This is a quantitative study that collects primary data from respondents via questionnaires, yielding 62 data points. This study's data analysis methods include descriptive analysis, multiple linear regression, t test, F test, and coefficient of determination test. The study's findings indicate that PT staff' performance is influenced by their work environment, leadership, and work discipline. BPR Gunung Merbabu Semarang Branch Office, partially or concurrently.